2009
DOI: 10.1111/j.1744-7402.2008.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Ablation Behavior of HfB2–SiC‐Based Ultra‐High‐Temperature Ceramics Under Severe Heat Conditions

Abstract: HfB 2 -SiC-based ultra-high-temperature ceramics with aluminum nitride (AlN) as a sintering aid were hot pressed at 18501C. The sinterability and mechanical properties were investigated and compared with the composite without a sintering aid. It was shown that the addition of AlN greatly improved the powder sinterability and enabled the production of a nearly full-dense composite. The mechanical properties, especially the flexural strength, were enhanced remarkably through the improvement in the sinterability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…SiC + 3/2O 2 = SiO 2 + CO(g) (2) that yield oxide by-products like zirconia (ZrO 2 ), boron oxide (B 2 O 3 ) and silica (SiO 2 ). Boron oxide, which melts at 450 • C, promptly mixes with SiO 2 for temperatures above 1200 • C to form a borosilicate glass that spreads over and seals the external surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SiC + 3/2O 2 = SiO 2 + CO(g) (2) that yield oxide by-products like zirconia (ZrO 2 ), boron oxide (B 2 O 3 ) and silica (SiO 2 ). Boron oxide, which melts at 450 • C, promptly mixes with SiO 2 for temperatures above 1200 • C to form a borosilicate glass that spreads over and seals the external surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high temperature ceramics (UHTCs) containing transition metal borides are under intensive analysis for applications in extreme environments, [1][2][3] where high-temperature aerospace applications on hypersonic vehicles have been the most investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al 2 O 3 , on the other hand, will persist at elevated temperatures, and is known to reduce the viscosity of silicates and will, therefore, possibly enhance the oxidation resistance . Furthermore, Li et al and Zhang et al reported improved ablation resistance with AlN addition. Therefore, it is important to ascertain the oxidation resistance of ZrB 2 –SiC modified by an alumina former such as AlN.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its remarkable properties of high melting point, Young's modulus, hardness, thermal conductivity, and excellent corrosion resistance, HfB 2 has been considered as a good potential material for ultrahigh temperature applications in the aerospace industry. [1][2][3] However, densification of monolithic HfB 2 is very difficult due to its high melting point, strong covalent bonding, and low self-diffusion rate. The densification of HfB 2 has been influenced by the properties of the HfB 2 powder, such as purity, morphology, surface area, and defects concentration.…”
Section: Introductionmentioning
confidence: 99%